Peningkatan Kemampuan Membaca Al-Qur’an Lansia Melalui Religious Literacy di Dusun Krajan Tukum Tekung Lumajang Tahun 2020 - Adrian, Adrian (UAS PRESS, 2021)
This research was related to religious literacy which was carried out to the elderly people as many as 8 people. That advanced age is a barrier to learning. The elderly people feel that it is very difficult for them to receive learning materials. While reading the Qur‟an for the elderly is a problem in itself. Many of the elderly people find it difficult that what they learn is not from their own language. In this case, as happened in Krajan Hamlet, Tukum Village RT 16 RW 17, many elderly cannot read the Qur‟an properly and correctly, but even so their enthusiams to learn to read the Qur‟an is very high. So far, it can be said that there are no teachers for the elderly in the hamlet. So far the elderly have only prayed, istighotsah, wiridanwiridan regularly and occasionally participate in the Qur‟an recitation activities with children and adolescents. Based on the description of problem identification, the objectives of this empowerment are : to improve the reading of the Qur‟an for the elderly, to provide awareness of the importance of reading the Qur‟an for the elderly and so that the elderly can be examples for their children. The method used in this study includes 4 stages : explorasi, create and action, evaluasi and report and dissemination. The results of this study after empowering religious literacy (reading the Qur‟an) for the elderly, then there is an optimal increase. It can be concluded that the empowerment carried out in Krajan Hamlet Tukum Village, is a religious education for the elderly which through the efforts made by the supervisor as well as the researcher includes : provide the sorogan method for the elderly, give examples of reading first, participants repeat the material that has been submitted by the supervisor and evaluate the participants